2019
DOI: 10.1021/acs.orglett.9b02862
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic, Enantioselective Reductive Bis-functionalization of Secondary Amides: One-Pot Construction of Chiral 2,2-Disubstituted 3-Iminoindoline

Abstract: We report the first catalytic, enantioselective reductive bis-functionalization of common amides, which provides a facile access to a variety of 2,2-disubstituted 3-iminoindolines in good yields and with excellent enantioselectivities. The reaction conditions are quite mild and can be run on a gram scale. In this one-pot reaction, three C–C bonds, one ring, and one nitrogen-containing tetrasubstituted carbon stereocenter are created in a catalytic enantioselective manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 56 publications
(19 reference statements)
0
17
0
1
Order By: Relevance
“…This method afforded comp heterocycles bearing a nitrogen-substituted quaternary and aminal stereogenic cente that are not trivial to make in 51-71% yields with >20:1 diastereoselectivities and 21-96 ee. In 2019, Zheng, Ye, Huang, and coworkers reported a one-pot construction of chi 2,2-disubstituted 3-iminoindolines (Scheme 9) [63]. In addition, 3-Iminoindoles (11) we generated in situ from amides and isocyanides in CH2Cl2 for 1 h, and then the resulti reaction mixtures were treated with a DMSO solution of ketones, proline and Et3N provide the Mannich products in 51-79% yields with 95-99% ee.…”
Section: R Peer Review 6 Of 45mentioning
confidence: 99%
See 1 more Smart Citation
“…This method afforded comp heterocycles bearing a nitrogen-substituted quaternary and aminal stereogenic cente that are not trivial to make in 51-71% yields with >20:1 diastereoselectivities and 21-96 ee. In 2019, Zheng, Ye, Huang, and coworkers reported a one-pot construction of chi 2,2-disubstituted 3-iminoindolines (Scheme 9) [63]. In addition, 3-Iminoindoles (11) we generated in situ from amides and isocyanides in CH2Cl2 for 1 h, and then the resulti reaction mixtures were treated with a DMSO solution of ketones, proline and Et3N provide the Mannich products in 51-79% yields with 95-99% ee.…”
Section: R Peer Review 6 Of 45mentioning
confidence: 99%
“…In addition, 3-Iminoindoles (11) we generated in situ from amides and isocyanides in CH2Cl2 for 1 h, and then the resulti reaction mixtures were treated with a DMSO solution of ketones, proline and Et3N provide the Mannich products in 51-79% yields with 95-99% ee. This method construct 3 carbon-carbon bonds, 1 ring, and 1 nitrogen-substituted quaternary stereogenic cen In 2019, Zheng, Ye, Huang, and coworkers reported a one-pot construction of chiral 2,2-disubstituted 3-iminoindolines (Scheme 9) [63]. In addition, 3-Iminoindoles (11) were generated in situ from amides and isocyanides in CH 2 Cl 2 for 1 h, and then the resulting reaction mixtures were treated with a DMSO solution of ketones, proline and Et 3 N to provide the Mannich products in 51-79% yields with 95-99% ee.…”
Section: R Peer Review 6 Of 45mentioning
confidence: 99%
“…[33][34][35] Particularly, an interesting l-proline-catalyzed reductive bisfunctionalization of secondary amides for one-pot construction of chiral 2,2-disubstituted 3-iminoindoline has been developed recently. 36 Alternatively, the seminal catalytic reductive functionalization of amides with silane reagents has emerged. IrCl(CO)(PPh 3 ) 2 [37][38][39][40][41][42][43][44] and Mo(CO) 6 [45][46][47] have been developed as effective catalysts for the hydrosilylation of amides, thus diversifying the reaction of reductive functionalization of amides…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the high stability of amides, synthetically useful methods are either multi-step transformations or required harsh conditions [1]. In recent years, the direct transformation of amides has attracted considerable attention, which resulted in many mild and useful C-C bond forming methods [2,3] including the catalytic ones [4]. As for the transformation of amides into esters, in 1998, Charette et al [5a] and Dossena et al [5b] independently reported a mild method for the one-pot transformation of amides into esters, which features the in situ activation of amides with a stoichiometric amount of triflic anhydride.…”
Section: Introductionmentioning
confidence: 99%